The Design of Minoxidil Microemulsion Formulation and the Effects of Ingredients on the Permeability of Rat Skin and Its Physicochemical Properties - Anayatollah Salimi; Eskandar Moghimipour; Ali Talebpour Jahromi; Saeed Mohammad Soleymani (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: Minoxidil is one of the agents that can treat hair growth disorders, including alopecia, by increasing the anagen period. Due to the nature of minoxidil, the permeability of the drug to the skin surface is negligible. Therefore, the purpose of this study was to design and evaluate microemulsion formulations in order to increase skin permeability of minoxidil. Materials and methods: Microemulsions containing 2% minoxidil were prepared with an appropriate amount of oil phase, surfactant, and co-surfactant. The medicinal substance was dissolved in the oily phase. The physicochemical properties of the microemulsions, including particle size, viscosity, release, skin permeation through rat skin as well as the rate of drug permeation through rat skin, were evaluated using Franz cells. Results: The particle size of microemulsions was in the range of 5.45-10.4 nm, viscosity was 113.2-199.2 centipoise. This study showed that the parameters of drug release percentage in the second hour, drug release percentage in the 24th hour, viscosity and Dapp were significantly related to independent variables(P<0.05). Increasing the percentage of water and the percentage of oil has increased the amount of drug release in 24 hours. Increasing the percentage of oil and decreasing the percentage of water can lead to an increase in viscosity, and increasing the percentage of water can increase the amount of Dapp in microemulsions. Conclusion: The prepared formulations were able to significantly increase the skin permeability of minoxidil.